Integration of the ASSURE Model for Bachelor of Nursing Training: An International Project - Nataliya A. Kasimovskaya; Carol Chabrera; Saara Laaksonen; Tiina Pelander; Gregor Štiglic; Natalia S. Geraskina; Eva Schulc; Esther Cabrera (National Research Mordova State University, 2021)
Introduction. The active integration of digital technologies into the modern educational process is an urgent task for the global education ecosystem. In this paper, within the framework of the joint international educational project "Digital Toolbox for Innovation in Nursing Education (I-BOX)", conducted under the Erasmus+ Programme of the European Union, we present a new instructional design of the educational process using digital technologies on an electronic platform, based on the ASSURE model. The aim of the study is to design digital educational process using the ASSURE model with a view of its integration into electronic platforms. Materials and Methods. The development of the ASSURE model for instructional design was based on three stages. The first stage involved the analysis of available instructional models in order to determine the feasibility of application for the project. The second stage included the adaptation of the ASSURE model for instructional design as consistent with the project objectives. The third stage covered the definition and integration of modern digital technologies in the process of instructional design following the ASSURE model. Results. Based on the results of the study, the participants of the I-BOX Strategic Partnership Consortium developed an ASSURE model that can be applied for the instructional design in educational process when the use of digital technologies (video, audio, podcasts) and the placement of learning materials on an electronic platform are required. Project participants developed a guide "ASSURE MODEL: Conceptual Structure of the Project and Assessment" based on the results of the study with a step-by-step description of the ASSURE model for the e-learning process. The developed educational and audiovisual e-learning materials based on the ASSURE model will be available on the electronic platform. Discussion and Conclusion. The materials of the paper will be useful when designing the educational process on an electronic platform or in an online format. The presented ASSURE model will increase the possibilities and effectiveness of teaching students from different countries using digital technologies on electronic platforms.